THE TECHNOLOGY OF UTILIZING THE PEDAGOGICAL VIEWS OF CENTRAL ASIAN THINKERS IN THE EDUCATIONAL PROCESS (Intent Research Scientific Journal, 2025)
In the article, the pedagogical views of the thinkers of Central Asia are studied and analyzed, the technology of using them in the process of education, the possibilities of their adaptation to the requirements of today's times.